2009
DOI: 10.1097/ta.0b013e31818b146d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Delayed Wound Healing by Commonly Used Antiseptics

Abstract: When debridement of the wound bed is not sufficient to reduce bacterial loads, the application of broad-spectrum antiseptics maybe indicated. Our data would suggest that H2O2 and iodine are poor choices, potentially retarding the contribution of fibroblasts to the healing process. Silver sulfadiazine and chlorhexidine, at levels still proven to be bactericidal, had fewer detrimental effects on fibroblast activity in these assays. The silver-containing antiseptics may even increase the proliferative potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
103
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 35 publications
3
103
0
5
Order By: Relevance
“…In addition, the killing ability of H 2 O 2 on pathogenic bacteria like Pseudomonas aeruginosa is doubtful because catalases are reported to exist in their bodies [55] . H 2 O 2 is also used regularly to prepare the bony bed in cemented arthroplasties as well as to achieve hemostasis in neurosurgery [56,57] .…”
Section: Current Clinical Use Of Hydrogen Peroxidementioning
confidence: 99%
“…In addition, the killing ability of H 2 O 2 on pathogenic bacteria like Pseudomonas aeruginosa is doubtful because catalases are reported to exist in their bodies [55] . H 2 O 2 is also used regularly to prepare the bony bed in cemented arthroplasties as well as to achieve hemostasis in neurosurgery [56,57] .…”
Section: Current Clinical Use Of Hydrogen Peroxidementioning
confidence: 99%
“…Wound management entails a hospital stay of specific duration, expensive medication and various surgical modalities followed by a long process of rehabilitation (Thomas et al 2009). Most topical antibacterial agents and disinfectants are effective in protecting against infections, but the occurrence of irritations in the skin and allergy due to these agents reduces the rate of skin regeneration and increases the time needed for complete recovery (Burks 1998).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is no consensus amongst wound care authorities on the advantages of using sterile solutions over non-sterile solutions. Research has also established that the use of antiseptic solutions may compromise the healing process (Thomas et al, 2009) and, as a result, the use of normal saline as a cleansing solution is widely recommended (Lawrence, 1997). In fact, preparations with antiseptic properties have also been traditionally used since the earliest times; however, published research has suggested that antiseptic solutions may hinder the healing process.…”
Section: Introductionmentioning
confidence: 99%